Penerapan Model Project Based Learning (PjBL) Untuk Meningkatkan Kemampuan Komunikasi Matematis Kelas IV SD - Nelsyam, Anida Putri; Zainil, Melva (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2016)
This study aims to describe the application of the Project Based Learning (PjBL) model to improve mathematical communication skills in the presentation of data in Grade IV Elementary School. The type of research is Classroom Action Research (CAR) using qualitative and quantitative approaches. The research subjects were teachers and 24 students in the fourth grade of elementary school 20 Kalumbuk. The results showed an increase. In the first cycle the results of the RPP observation from 82.1% to 92.9% in the second cycle. The implementation in the aspects of teachers and students in the first cycle was 71.9% to 93.8% in the second cycle. The average assessment of mathematical communication skills of students in the first cycle of 73.82 to 90.00 in the second cycle.